Elevating Employee Performance: The Role of Organizational Culture and Competence: Study at One of The Government Agencies in Bandung - Deni Dwi Mardeni; Aan Hardiyana (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
The study's findings illuminate the crucial connection between employee performance, compensation, and organizational culture in a West Javan government agency, are of significant importance. It was determined by examining the information gathered from surveys and questionnaires that Organizational Culture and Compensation are important factors in determining how well employees perform in the workplace. According to the study, fair and motivating compensation packages combined with a supportive and upbeat corporate culture can greatly increase worker productivity and job satisfaction. The study's conclusions also highlight how crucial it is for management to consistently seek to create a welcoming workplace that supports a solid corporate culture and offers competitive pay to staff members. Government organizations in West Java can increase staff performance and overall organizational effectiveness and efficiency by prioritizing these factors. To guarantee long-term beneficial results for the organization and its employees, management must consider these insights and act proactively to preserve and improve organizational culture and compensation.